MENIMBUN BARANG (IHTIKAR) PERSPEKTIF HADIS (SUATU KAJIAN TEMATIK) - Andi Intan Cahyani (Jurusan Hukum Ekonomi Syariah Fakultas Syariah dan Hukum Uin Alauddin Makassar, 2020)
AbstractHadith research on ihtikar and especially on the hadith relating to the forbidden ihtikar which is the object of research in this paper is the quality of authentic Hadith, both viewed from the sanad and its mature quality. Therefore, this hadith can be used as a legal basis in establishing Islamic law. The Hadith states the prohibition on doing ihtikar with the phrase